(untitled) (International Journal of Food and Nutritional Sciences, 2021)
The Smart Vehicle Alert Communication System (SVACS) represents a groundbreaking technological advancement in the realm of transportation and road safety. This system integrates an array of sophisticated sensors, advanced communication protocols, data analytics, and autonomous capabilities to elevate the driving experience, optimize traffic management, and, most crucially, enhance road safety. Through a comprehensive literature review, we have explored the multifaceted dimensions of SVACS. This technology stands poised to address one of the leading causes of accidents: human error. By equipping vehicles with an assortment of sensors, including LiDAR, radar, and cameras, SVACS enables real-time detection of potential hazards. Concurrently, vehicle-to-vehicle (V2V) and vehicle-to-infrastructure (V2I) communication protocols empower instantaneous data exchange, facilitating proactive collision avoidance and traffic management. However, the realization of SVACS’s potential is accompanied by a set of formidable challenges. These include navigating the intricacies of data privacy and cybersecurity, establishing regulatory compliance and ethical frameworks, and fostering user trust and acceptance. It is paramount to address these hurdles to ensure responsible SVACS deployment and safeguard the privacy and security of user data. SVACS’s transformative impact on transportation cannot be overstated. It holds the promise of reducing accidents, alleviating traffic congestion, and creating a more environmentally friendly and efficient mobility landscape. The ongoing journey of SVACS is marked by research, innovation, and collaboration among diverse stakeholders, ushering in a future where vehicles become intelligent companions dedicated to ensuring our safety and improving our journey on the road